Pengembangan Video Tutorial Dampak Penggunaan Zat Aditif Pada Makanan Dan Minuman Mata Pelajaran IPA Sekolah Menengah Pertama - Andriyana, Hena; Indryani, Indryani; Ali, Muhammad; Indrayana, Boy; Yuliawan, Ely (Universitas Batanghari Jambi, 2024)
The purpose of this study was to evaluate the development of video tutorials for junior high school science classes about the impacts of additive use on food and beverages, as well as to gauge the effectiveness of the tutorials. The five steps of the ADDIE development model analysis, design, development, implementation, and evaluation are used in this work. This study discovered that junior high school science classes have gone through multiple phases of developing video lessons on the impacts of utilising chemicals on food and beverages. Among them are validation from material experts, which received a very decent rating of 95.4 percent, and validation from media experts, which received a decent assessment of 86.4 percent. Field trials were conducted to measure the effectiveness of this video tutorial media. This includes a 93% science teacher trial with very decent assessments; a small group trial with 9 students showed a result of 84.8% with a decent assessment; and a large group trial with 25 students from class IX C at SMP Negeri 1 Muaro Jambi showed a result of 90.8% with a decent assessment. This development shows that video tutorials on the effects of additive use on food and beverages, especially those related to science lessons in junior high school, can be considered a feasible, efficient, and high-quality learning method. This development shows that video tutorials on the effects of additive use on food and beverages, especially those related to science lessons in junior high school, can be considered as feasible, efficient, and high-quality learning methods. Based on this development, it is suggested that many people, especially science teachers in junior high schools, consider using this video tutorial as one of the most useful learning media. Therefore, it is expected to increase students' understanding and interest in learning about the impact of the use of additives on food and beverages in science studies.